Canadian Labor Today: Partial Successes, Real Challenges - Brennan, Barry (Monthly Review: An Independent Socialist Magazine, 2005)
Analyzes the conflicted terrain of the Canadian labour movement as a result of neoliberal restructuring of the economy and the frayed relationship with the social democratic NDP. Compares union densities in Canada and the US. Concludes that transformative union renewal must include the political rebuilding of a worker-based socialist movement.
Keywords: Canada; Canadian Auto Workers (CAW); Economic conditions; Labor Unions; Labor movement; Labor union members; New Democratic Party (NDP); Organizational structure

Abstracts / Résumés [55, Spring/Printemps 2005] (Labour / Le Travail, 2005)
English/French abstracts of the articles in the current issue.

Abstracts = Résumés (56, Fall 2005) (Labour / Le Travail, 2005)
English/French abstracts of articles in the Spring 2015 issue.
Keywords: ABSTRACTS; BIOGRAPHIES – Abstracts; Communism; Ethnicity; Working class

Taking Back the Streets: Women, Youth, and Direct Democracy - Ackelsberg, Martha (Labour / Le Travail, 2005)
The article reviews the book, "Taking Back the Streets: Women, Youth, and Direct Democracy," by Temma Kaplan.

Organizing Wal-Mart: The Canadian Campaign - Adams, Roy J. (Just Labour: A Canadian Journal of Work and Society, 2005)
The central focus of this article is the effort by Canadian unions to organize Wal-Mart. Organizing the world's largest corporation is considered to be critical because the company's business "template" calls for wages and benefits considerably inferior to those of unionized workers. To date, although a few bargaining units have been certified, Wal-Mart has managed to thwart all attempts to negotiate collective agreements. However, because the United Food and Commercial Workers have certified units in a few provinces with first contract arbitration, the achievement, eventually, of a collective agreement appears to be likely.

Cleaners and Pop Culture Representation - Aguiar, Luis L M (Just Labour: A Canadian Journal of Work and Society, 2005)
Building cleaners are increasingly portrayed in pop culture. This article seeks to provide reasons for their increased visibility, and then examines precisely how they are constructed. The analysis reveals three overriding themes of representation: (1) cleaners as a discourse for Americanism; (2) cleaners as stand ins for the rehabilitation of ‘whiteness’; and (3) cleaners as endure the neoliberal workplace.

The Montreal Massacre: A Story of Membership Categorization Analysis - Atwood, Kristin (Labour / Le Travail, 2005)
The article reviews the book, "The Montreal Massacre: A Story of Membership Categorization Analysis," by Peter Eglin and Stephen Hester.

Industrial Sunset: The Making of North America's Rust Belt, 1969-1984 - Ayres, Jeffrey (Labour / Le Travail, 2005)
The article reviews the book, "Industrial Sunset: The Making of North America's Rust Belt, 1969-1984." by Steven C. High.

Training the Excluded for Work: Access and Equity for Women, Immigrants, First Nations, Youth, and People with Low Income - Baines, Donna (Labour / Le Travail, 2005)
The article reviews the book, "Training the Excluded for Work: Access and Equity for Women, Immigrants, First Nations, Youth, and People with Low Income," edited by Marjorie Griffin Cohen.

Imperialism and its Discontents - Bakan, Abigail B. (Labour / Le Travail, 2005)
The article reviews and comments on "The Clash of Fundamentalisms: Crusades, Jihads and Modernity" by Tariq Ali, "The Clash of Barbarisms: September 11 and the Making of the New World Disorder" by Gilbert Achcar , "Welcome to the Desert of the Real" by Slavoj Zizek's, "The New Rulers of the World" by John Pilger, and "The New Mandarins of American Power" by Alex Callinicos.

Caetana Says No: Women's Stories from a Brazilian Slave Society - Barbosa, Rosana (Labour / Le Travail, 2005)
The article reviews the book, "Caetana Says No: Women's Stories from a Brazilian Slave Society," by Sandra Lauderdale Graham.

Architecture de ressources humaines : Perspectives théoriques et pistes de recherche - Barrette, Jacques (Relations industrielles / Industrial Relations, 2005)
Le domaine de la gestion stratégique des ressources humaines manque d’encadrement théorique en ce qui concerne le caractère unique de l’architecture de ressources humaines (RH). L’article propose une réflexion théorique sur cette notion et ses deux dimensions principales : l’alignement vertical et la cohérence horizontale. L’exposé explique comment et pourquoi les organisations de même type possèdent sensiblement la même architecture RH. L’importance du rôle des contingences internes et des conditions de réalisation des objectifs RH est abordée. L’auteur explore le caractère unique de la GRH au niveau de la cohérence des pratiques et la complexité des liens avec l’alignement vertical. Un modèle combinant les deux dimensions de l’architecture RH propose des pistes de réflexion quant à leur effet interactif sur la performance organisationnelle. Des hypothèses et stratégies de recherche pour mesurer la présence et l’impact de la cohérence horizontale sur la performance organisationnelle sont suggérées.

Union Raiding and Organizing in Ontario - Bartkiw, Timothy J.; Martinello, Felice (Relations industrielles / Industrial Relations, 2005)
This paper provides the first analysis of aggregate raiding activity in Ontario by isolating raid applications from available certification data. Raiding in Ontario generally decreased over the 1975 to 2003 period save for the huge increases in 2000 and 2001 involving the CAW and SEIU. Bargaining units are significantly larger in raids, and legislative changes had little effect on aggregate raiding levels. Over most of the period raiding activity has been quite modest. Thus analyses of union organizing and its effect on union density are unlikely to be affected by leaving raids in the organizing data. An important exception occurs in 2000 and 2001, where the certification data seriously overstate new organizing. Corrected measures show that new (non-raid) union organizing continues to decline in Ontario. The decline in new organizing has been greater than the decline in raiding, resulting in an increased proportion of organizing due to raids in recent years.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical analysis; Union membership

The Segmentation of Academic Labour: A Canadian Example - Bauder, Harald (ACME: An International E-Journal for Critical Geographies, 2005)
Academia increasingly faces pressures of corporatization and flexibilization. Of particular concern is the segmentation of academic labour into stable tenured or tenure-track professors and “flexible” sessional and adjunct faculty. In this paper, I review evidence of the segmentation of the Canadian academic labour market, examine the conditions that permit segmentation to exist, discuss why academic geographers in both segments comply with a segmented labour market and, finally, propose potential strategies to address the issue of segmentation.
Keywords: Academia; Academic geographers; Corporatization; Faculty; Flexibilization; Segmentation

The Impact of Macroeconomic Conditions on the Instability and Long-Run Inequality of Workers' Earnings in Canada - Beach, Charles M.; Finnie, Ross; Gray, David (Relations industrielles / Industrial Relations, 2005)
This paper examines the variability of workers' earnings in Canada over the period 1982-1997. Using a large panel of tax file data, we decompose total variation in earnings across workers and time into a long-run inequality component between workers and an average earnings instability component over time for workers. We find an increase in earnings variability between 1982-89 and 1990-97 that is largely confined to men and largely driven by widening long-run earnings inequality. Second, the pattern of unemployment rate and GDP growth rate effects on these variance components is not consistent with conventional explanations and is suggestive of an alternative paradigm of how economic growth over this period widens long-run earnings inequality. Third, when unemployment rate and GDP growth rate effects are considered jointly, macroeconomic improvement is found to reduce the overall variability of earnings as the reduction in earnings instability outweighs the widening of long-run earnings inequality.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economic conditions; Economic impact; Economic models; Economic theory; Inequality; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Wages & salaries

Dignity at Work for Low Wage, Low Skill Service Workers - Berg, Peter; Frost, Ann C. (Relations industrielles / Industrial Relations, 2005)
Using responses from a telephone survey of 589 low wage, low skill workers in US hospitals, the authors investigate the workplace features that influence workers' perceptions of dignity at work. Both work organization variables and union representation are investigated as potential factors affecting workers' perceptions of fair treatment by their employer, intrinsically satisfying work, and economic security. Work organization and union representation have little effect on dignity at work with the exception of their association with higher wages and therefore a greater degree of economic security. Results indicate that higher pay, adequate levels of staffing and resources, and access to training are the variables that are most closely associated with dignity on the job.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Dignity; Labor Unions; Perceptions; Polls & surveys; Skills; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Variables; Wages & salaries

Le travail non qualifié : permanences et paradoxes - Bernier, Colette (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Le travail non qualifié : permanences et paradoxes," edited by Dominique Méda and Francis Vennat.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les PME québécoises et la formation : De l’effet de taille aux dispositifs institutionnels - Bernier, Colette (Relations industrielles / Industrial Relations, 2005)
À partir d’un questionnement concernant le faible investissement des PME en formation, cet article tente de démontrer l’importance de l’environnement institutionnel par rapport aux seuls effets de taille. Par une analyse systémique de divers facteurs pouvant expliquer la formation dans une quarantaine de PME, l’article met en relief l’existence de trois configurations d’entreprises ayant des rapports différenciés à la formation; celles-ci vont de l’entreprise familiale qui offre peu de formation à l’entreprise indépendante offrant une formation structurée en passant par diverses formes d’entreprises qui, sur la base de leur insertion sous des bannières ou franchises ou encore de l’action des comités sectoriels ou d’organismes régionaux, accordent une importance de plus en plus grande à la formation et la structurent en conséquence. L’article conclut sur la nécessité d’une prise en compte « systémique » des dispositifs institutionnels pour la mise en place de politiques publiques adéquates.

Contractors or Disguised Employees? : A Case Study of Couriers in Winnipeg - Bickerton, Geoff; Warskett, Rosemary (Just Labour: A Canadian Journal of Work and Society, 2005)
The courier industry in Canada is rapidly expanding. This is due to a number of factors including greater international trade in goods; more use of just-in-time inventory strategies; and the rapid development of internet commerce. Significant technological and organizational developments within the industry have led to greater segmentation of markets. As a result, large national and international parcel delivery firms dominate the international and intercity markets, while there has been a proliferation of smaller firms in the same-city, same-day markets. The research findings from a case study conducted in Winnipeg reveal that couriers in certain parts of the industry are relatively well paid, with benefits and employment conditions negotiated by their union, while others are independent contractors with low incomes, no benefits and insecure tenure. The article compares the experience of these two types of couriers and examines what is being done to improve the terms and conditions of work for same-day couriers. It is concluded that nature of the same day courier industry means that union organizing will be very difficult and there is no guarantee of success. Unionization, however, is a necessary prerequisite for the improvement of conditions and wages in this growing industry.

Community Unionism: A Strategy for Organizing in the New Economy - Black, Simon J. (New Labor Forum, 2005)
Focuses on considering community unionism as a strategy for labor organizing with emphasis on autonomous community-based labor group organizational model. Background on the concept of community unionism; Information on the two examples of community unionism, the Ontario Coalition Against Poverty and the National Mobilization Against Sweatshops; Limitation of community unionism in making the type of economic gains for their members that a trade union can through collective bargaining.
Keywords: AUTONOMY (Political science); COMMUNITY organization; Collective bargaining; LABOR organizing; Labor

La gestion environnementale et la norme ISO 14 001 - Boiral, Olivier (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "La gestion environnementale et la norme ISO 14 001," by Corinne Gendron.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Le malaise des soignants : le travail sous pression à l'hôpital - Bonneville, Luc (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Le malaise des soignants : le travail sous pression à l’hôpital," by Yvan Sainsaulieu.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les cadres : grandeur et incertitudes - Bouffartigue, Paul (Relations industrielles / Industrial Relations, 2005)
The article reviews the book,"Les cadres : grandeur et incertitudes," by Olivier Cousin.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Psychosocial Work Environment and Certified Sick Leave among Nurses during Organizational Changes and Downsizing - Bourbonnais, Renée; Brisson, Chantal; Vézina, Michel; Masse, Benoît; Blanchette, Caty (Relations industrielles / Industrial Relations, 2005)
The study aimed to determine whether the incidence and duration of certified sick leave (CSL) among nurses had increased during major restructuring of the health care system in the province of Quebec, and to determine whether nurses exposed to adverse psychosocial factors at work showed an increased incidence of CSL. It involved nurses working in 13 health facilities. Sickness absence data were retrieved from administrative files (n = 1454). Incidence of CSL for all diagnoses and for mental health problems was examined. Telephone interviews were conducted to measure psychosocial factors at work with validated instruments. There was an increase in CSL among nurses during the restructuring, particularly for mental health problems. Modifiable adverse psychosocial work factors were identified and provide basis for interventions. Since human resources are the mainstay and primary resource of the health network, it is essential that people be able to perform their work under optimal conditions.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Nurses; Organizational change; Psychological aspects; Sick leave; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social aspects; Studies

Réflexions croisées sur la gestion des compétences en France et en Amérique du Nord - Bouteiller, Dominique; Gilbert, Patrick (Relations industrielles / Industrial Relations, 2005)
Si la gestion des compétences est encore un sujet d’actualité à la fois pour les gestionnaires de ressources humaines et pour bon nombre de responsables d’entreprise, c’est que l’objet même de cette gestion ne cesse de prendre de l’importante au sein des nouveaux systèmes productifs et face aux nouvelles contraintes de l’environnement. Pourtant, ces nouvelles approches, dont on parle beaucoup, sont peu et mal connues, et ne sont que très rarement mises en perspective au plan international. Il peut donc être intéressant, partant d’un enjeu « théoriquement » similaire — la compétence — de voir de quelle façon ces logiques et ces modes de gestion ont été conceptualisés, instrumentés et implantés de chaque côté de l’Atlantique. L’analyse conduit à observer que si les deux systèmes se sont constitués de façon contingente, et que certains facteurs lourds leur sont encore associés aujourd’hui, d’autres forces poussent vers une certaine standardisation, pour ne pas dire universalisation des approches dans ce domaine désormais central de la gestion des ressources humaines.

Masters, Servants, and Magistrates in Britain and the Empire, 1562-1955 - Bright, David (Labour / Le Travail, 2005)
The article reviews the book, "Masters, Servants, and Magistrates in Britain and the Empire, 1562-1955," edited by Douglas Hay and Paul Craven.

Emmeline Pankhurst: A Biography - Brooke, Stephen (Labour / Le Travail, 2005)
The article reviews the book, "Emmeline Pankhurst: A Biography," by June Purvis.

Florence Nightingale and the Health of the Raj - Brouwer, Ruth Compton (Labour / Le Travail, 2005)
The article reviews the book, "Florence Nightingale and the Health of the Raj," by Jharna Gourlay.

Handbook of Work Stress - Burke, Ronald J. (Relations industrielles / Industrial Relations, 2005)
The book Handbook of Work Stress, by Julian Barling, E. Kevin Kelloway, and Michael R. Frone, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Stress; Working conditions

Pensions and Public - Private Partnerships: A Cautionary Note for Union Trustees - Calvert, John (Just Labour: A Canadian Journal of Work and Society, 2005)
A major demand of public sector unions in recent years has been for greater control over their members’ pension plans. Recently, several provincial governments, most notably British Columbia, have agreed to joint trusteeship, a development which gives union trustees a voice in investment policy. This article focuses on the implications for union trustees of investments in Public Private Partnerships (P-3s) and related privatization initiatives. Examples of such investments include: transportation infrastructure projects, hospitals and health services, schools, municipal water and sewer systems, electrical utilities, and other projects that, historically, have been within the public sector. It argues that trustees should be wary of such investments. Public sector unions have criticized privatization initiatives as a threat to public sector jobs and services. P-3 investments are problematic because they may threaten the jobs of their union’s members, undermine the credibility of their union’s public policy objections to privatization and, in the end, may prove far more risky than P-3 promoters contend.

Multitude: War and Democracy in the Age of Empire - Camfield, David (Labour / Le Travail, 2005)
The article reviews the book, "Multitude: War and Democracy in the Age of Empire," by Michael Hardt and Antonio Negri.

Renewing the Study of Public Sector Unions in Canada. - Camfield, David (Socialist Studies/Études Socialistes, 2005)
A renewal of the study of public sector unionism in Canada is long overdue. This article explains why public sector unions deserve more attention from researchers than they have received of late and proposes that studies of public sector unions would benefit from adopting a new theoretical framework that conceptualizes contemporary unions as not only labour relations institutions but also as particular kinds of working-class movement organizations within a historically-specific class formation. It also identifies two obstacles to the production of accounts of contemporary public sector unions from this perspective.

What's Class Got To Do With It? American Society in the Twenty-First Century - Camfield, David (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "What's Class Got to Do with It? American Society in the Twenty-First Century," edited by Michael Zweig.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Essays; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social classes

Les syndicats français pris dans le tourbillon de la négociation collective - Catlla, Michel (Just Labour: A Canadian Journal of Work and Society, 2005)
Le présent article interroge l'action syndicale en France dans un contexte caractérisé par une remise en cause de la loi relative à la réduction de la durée du travail. En prenant appui sur le cas d'un établissement qui s'engage dans un processus d'allongement de la durée du travail, l'auteur retrace le cheminement parcouru par les acteurs en présence qui débute par la renégociation de la règle sur les 35 heures pour aboutir à l'invention d'une nouvelle régulation entre salariés et direction. Loin d'abroger les lois Aubry, ce mouvement d'allongement de la durée du travail questionne la capacité des acteurs à mener des négociations collectives. // This paper questions the way French trade unions have dealt with the effects of the legislation purporting to limit maximum working time to 35 hours per week. The research is based on a case study of a manufacturing firm. The author examines the ways in which local actors evolved from the negotiation over the implementation of the 35 hour work week to the development of new relationships between the employees and their employer. In this specific case study, the negotiation actually ended up lengthening working time. This result does not deny the importance of working time legislation but it does call into question the capacity of local unions to achieve in collective bargaining the objectives set out legislatively.

Workplace Equality: International Perspectives on Legislation, Policy and Practice - Chicha, Marie-Thérèse; Charest, Éric (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Workplace Equality: International Perspectives on Legislation, Policy, and Practice," edited by Carol Agocs.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; Equality; International comparisons; Labor Unions; Legislation; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social policy

‘Because they have all the power and I have none’: State restructuring of income and employment supports and disabled women's lives in Ontario, Canada. - Chouinard, Vera; Crooks, Valorie A. (Disability & Society, 2005)
We examine the connections between neo-liberal forms of state restructuring and intervention in disabled people’s lives, looking in particular at how these have affected disabled women’s experi- ences of an income support program, the Ontario Disability Support Program (ODSP), in Ontario, Canada. We first outline why and how state programs have been re-designed and imple- mented in increasingly harsh ways as a result of such neo-liberal forms of state restructuring. Even groups formerly considered among the ‘deserving poor’ have found their access to social assistance diminished. We then argue that this is an outcome of state programs, policies and practices which are re-asserting and more deeply entrenching ‘ableness’ as a necessary condition of citizenship, inclusion and access to justice. Finally, we illustrate how disabled women’s lives and well-being have been altered as a result of changes in the provision of these forms of state assistance using in- depth semi-structured interviews conducted with 10 women in Ontario.

Farm to Factory: A Reinterprétation of the Soviet Industrial Revolution - Clarke, Simon (Labour / Le Travail, 2005)
The article reviews the book, "Farm to Factory: A Reinterprétation of the Soviet Industrial Revolution," by Robert C. Allen.

Industrial Relations in China - Clarke, Simon (Labour / Le Travail, 2005)
The article reviews the book, "Industrial Relations in China," by Bill Taylor, Chang Kai and Li Qi.

Dual Commitment to the Organization and the Union: A Multi-Dimensional Approach - Cohen, Aaron (Relations industrielles / Industrial Relations, 2005)
This study examines the multi-dimensional nature of the dual commitment to the organization and the union. Most research that has examined this concept has used only one dimension for each commitment. The most established, multi-dimensional scales of organizational and union commitment were examined in their relationship to work and union correlates. The participants were 489 members (a 65% response rate) of the Union of Nurses in Israel. The findings showed that while affective commitment and union loyalty are related to the correlates examined here, the additional dimensions added significant variance to the results already explained by affective commitment and union loyalty. For example, normative commitment is related to four correlates and the variable "willingness to work for the union" is also strongly related to the correlates. The study concluded that utilizing only one dimension to examine each commitment might result in the loss of valuable information on dual commitment.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Commitments; Employee attitude; Labor Unions; Nurses; Organizations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Workers

CCF Colonialism in Northern Saskatchewan: Battling Parish Priests, Bootleggers and Fur Sharks - Collier, Ken (Labour / Le Travail, 2005)
The article reviews the book, "CCF Colonialism in Northern Saskatchewan: Battling Parish Priests, Bootleggers, and Fur Sharks," by David M. Quiring.

From Consent to Coercion: The Assault on Trade Union Freedoms, 3rd edition - Compa, Lance (Relations industrielles / Industrial Relations, 2005)
The book From Consent to Coercion: The Assault on Trade Union Freedoms, 3rd edition, by Leo Panitch and Donald Swartz, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

La citoyenneté au travail ? Une introduction = Towards Citizenship at Work? An Introduction - Coutu, Michel; Murray, Gregor (Relations industrielles / Industrial Relations, 2005)
Editorial introduction to the issue.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Making Public Pasts: The Contested Terrain of Montreal's Public Memories, 1891-1930 - Cupido, Robert (Labour / Le Travail, 2005)
The article reviews the book, "Making Public Pasts: The Contested Terrain of Montreal's Public Memories, 1891-1930," by Alan Gordon.

The Internet in the Workplace : How New Technology is Transforming Work - d'Iribarne, Alain (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "The Internet in the Workplace : How New Technology is Transforming Work," by Patricia Wallace.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Working Children Around the World: Child Rights and Child Reality - Dillon, Sara (Relations industrielles / Industrial Relations, 2005)
The article reviews the book. "Working Children Around the World: Child Rights and Child Reality," by G.K. Lieten.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Child labor; Essays; HUMAN rights; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Working conditions

Trade Unions in Europe: Meeting the Challenge - Doellgast, Virginia (Labour / Le Travail, 2005)
The article reviews the book, "Trade Unions in Europe: Meeting the Challenge," edited by Deborah Foster and Peter Scott.

L'économie sociale dans les services à domicile - Domin, Jean-Paul (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "L’économie sociale dans les services à domicile," edited by Yves Vaillancourt, François Aubry and Christian Jetté.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Publication Bias in Union-Productivity Research? - Doucouliagos, Hristos; Laroche, Patrice; Stanley, T. D. (Relations industrielles / Industrial Relations, 2005)
This paper develops and applies several meta-analytic techniques to investigate the presence of publication bias in industrial relations research, specifically in the union-productivity effects literature. Publication bias arises when statistically insignificant results are suppressed or when results satisfying prior expectations are given preference. Like most fields, research in industrial relations is vulnerable to publication bias. Unlike other fields such as economics, there is no evidence of publication bias in the union-productivity literature, as a whole. However, there are pockets of publication selection, as well as negative autoregression, confirming the controversial nature of this area of research. Meta-regression analysis reveals evidence of publication bias (or selection) among US studies.
Keywords: Bias; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economic conditions; Labor Unions; Productivity; Research methodology; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

The North Korean Revolution, 1945-1950 - Endicott, Stephen (Labour / Le Travail, 2005)
The article reviews the book, "The North Korean Revolution, 1945-1950," by Charles K. Armstrong.

Global Unions: Past Efforts and Future Prospects - Fairbrother, Peter; Hammer, Nikolaus (Relations industrielles / Industrial Relations, 2005)
International trade unionism faces a major challenge. Historically, Global Union Federations have been small and relatively remote international union secretariats with limited capacity to mobilize and speak on behalf of local members. However, with the changing architecture of international capital and nation states, these union bodies have started to renew themselves. The argument is that the emergent political economy provides the base upon which these unions can begin to campaign and represent members in more dynamic ways than in the past. Critical to these developments has been the promulgation of International Framework Agreements which adapt and extend familiar tools of representation. The outcome is the possibility of a multi-faceted form of trade unionism.
Keywords: Agreements; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; International; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

In Practice: Studies in the Language and Culture of Popular Politics in Modern Britain - Fielding, Steven (Labour / Le Travail, 2005)
The article reviews the book, "In Practice: Studies in the Language and Culture of Popular Politics in Modern Britain," by James Epstein.

Jobs and Incomes in a Globalizing World - Fields, Gary S. (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Jobs and Incomes in a Globalizing World," by Ajit K. Ghose.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Globalization; LABOR market; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Wages & salaries

Book Notes [56, Fall 2005] - Finkel, Alvin (Labour / Le Travail, 2005)
The article briefly reviews M. Ann Hall's "The Girl and the Game: A History of Women’s Sport in Canada;" Hugh D. Hinman's "Child Labour: An American History;" Robert Michael Smith's "From Blackjacks to Briefcases: A History of Commercialized Strikebreaking and Unionbusting in the United States;" P.W. Singer's "Corporate Warriors: The Rise of the Privatized Military Industry;" Andrew Hemingway's "Artists on the Left: American Artists and the Communist Movement, 1926-1956;" "Why Do People Hate America?" by Ziauddin Sardar and Merryl Wyn Davies; Robert J. Alexander's "A History of Organized Labor in Brazil;" Richard D. Salvatore's "Wandering Paysanos: State Order and Subaltern Experience in Buenos Aires During the Rosas Era;" Juanita de Barros's "Order and Place in a Colonial City: Patterns of Struggle and Resistance in Georgetown, British Guiana, 1889-1924;" "Negotiations and Change: From the Workplace to Society," by Thomas A. Kochan and David B. Lipsky; and Carl Freedman's "The Incomplete Projects: Marxism, Modernity, and the Politics of Culture."

'Enough to Keep Them Alive': Indian Welfare in Canada, 1873-1965 - Finkel, Alvin (Labour / Le Travail, 2005)
The article reviews the book, "'Enough to Keep Them Alive':Indian Welfare in Canada, 1873-1965," by Hugh Shewell.

From UI to EI: Waging War on the Welfare State - Finkel, Alvin (Labour / Le Travail, 2005)
The article reviews the book, "From UI to EI: Waging War on the Welfare State," by Georges Campeau.

Message in a Bottle: The Making of Fetal Alcohol Syndrome - Finkel, Alvin (Labour / Le Travail, 2005)
The article reviews the book, "Message in a Bottle: The Making of Fetal Alcohol Syndrome," by Janet Golden.

The Myth of the Good War: America in the Second World War - Finkel, Alvin (Labour / Le Travail, 2005)
The article reviews the book, "The Myth of the Good War: America in the Second World War," by Jacques R. Pauwels.

Silence on the Mountain: Stories of Terror, Betrayal and Forgetting in Guatemala - Forster, Cindy (Labour / Le Travail, 2005)
The article reviews the book, "Silence on the Mountain: Stories of Terror, Betrayal and Forgetting in Guatemala," by Daniel Wilkinson.

Psychologie de la formation, jalons et perspectives - Fournier, Pierre-Sébastien (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Psychologie de la formation, jalons et perspectives," by Jacques Leplat.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Theorizing Historical Consciousness - Frank, David (Labour / Le Travail, 2005)
The article reviews the book, "Theorizing Historical Consciousness," edited by Peter Seixas.

Saint-Laurent: La Main de Montréal - Frenette, Yves (Labour / Le Travail, 2005)
The article reviews the book, "Saint-Laurent: La Main de Montréal," by Pierre Anctil.

After Industrial Citizenship: Market Citizenship or Citizenship at Work? - Fudge, Judy (Relations industrielles / Industrial Relations, 2005)
This article sketches the rise and fall of industrial citizenship in Canada, and presents two very different models of citizenship that might replace it. It begins by defining the concept of citizenship, and explaining how industrial citizenship has conventionally been understood. It then traces the genealogy of industrial citizenship in Canadian labour law, and how the processes of feminization, deregulation, and globalization have challenged it as a normative ideal and undermined the conditions that have sustained it. The article concludes by considering two scenarios for industrial citizenship in the future: one in which the substance of citizenship is circumscribed by an emphasis on the market, and the other in which citizenship is extended beyond employment to work.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Citizenship; HUMAN rights; Labor Unions; Labor law; Models; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Workers

Public Sector Employment and Gender Wage Inequalities in British Columbia: Assessing the Effects of a Shrinking Public Sector - Fuller, Sylvia (The Canadian Journal of Sociology, 2005)
The public sector is an important employer of women in Canada, particularly at the provincial level. As a result, recent initiatives to cut employment in this sector have the potential to impact broader gender inequalities in the labour market. This study uses data from the Labour Force Survey to estimate provincial-level public and private sector wage differentials in British Columbia for men and women, and to assess the degree to which declines in public sector employment in B.C. may affect the overall gender wage gap. Results confirm that provincial public sector employment is both relatively more prevalent and advantageous for women than for men. Substantial declines in employment in this sector therefore have the potential to noticeably increase the gender wage gap.

Deference and Defiance in Monterrey: Workers, Paternalism, and Revolution in Mexico, 1890-1950 - Galleguillos, Nibaldo H. (Labour / Le Travail, 2005)
The article reviews the book, "Deference and Defiance in Monterrey: Workers, Paternalism, and Revolution in Mexico, 1890-1950," by Michael Snodgrass.

Work and Citizenship in Mexico in the Era of Globalization - García, Arnulfo Arteaga (Relations industrielles / Industrial Relations, 2005)
This article analyzes the case of Mexico in order to provide an overview of citizenship at work in the context of a dependent regional economy in a global era. It examines the framework of rights (civil, political and social) linked to the condition of the working class in a state-corporatist labour regulation model. It also explores the repercussions for workers, both at work and beyond the workplace, of current transitions from this model as well as looking at the redefinition of labour rights now taking place. Four different segments of the labour force are used to illustrate the nature of the historical and continuing deficit in the exercise of citizenship at work. This preliminary exploration leads to the identification of some paths for future research.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Citizenship; Globalization; Labor Unions; Labor law; Regulation; Rights; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social classes; Working conditions

The Blue Eagle at Work: Reclaiming Democratic Rights in the American Workplace - Gérin-Lajoie, Jean (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "The Blue Eagle at Work: Reclaiming Democratic Rights in the American Workplace," by Charles J. Morris.
Keywords: American history; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; Labor law; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Wagner Act 1935-US

"Stand by the Union, Mr. Arch": The Toronto Labour Establishment and the Emigration Mission of Britain's National Agricultural Labourers' Union - Goutor, David (Labour / Le Travail, 2005)
In the fall of 1873 Joseph Arch, the president of England's National Agricultural Labourers' Union (NALU), embarked on a mission to scout Canada as an emigration destination. He was received with much hospitality in Canada. Large-scale migration of British farmworkers had the support of an extraordinary consensus between the NALU, Canadian political and business elites, and Toronto labor leaders who wielded enormous influence over the labor movement in Ontario. The consensus was the result of developments in British agricultural unionism, Ontario's farming sector, Canada's immigration policy, and the Toronto labor establishment's approach to immigration. However, during the mission, tensions emerged between Arch and the Toronto labor establishment that strained the appearance of international union solidarity. These tensions revealed the treacherous nature of a relationship between labor leaders in an immigrant-receiving country and an organization, even a union, looking to promote emigration.

La négociation au travail - Greco, Luca (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "La négociation au travail," edited by Michèle Grosjean and Lorenza Mondada.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

British Trade Unions since 1933 - Griffiths, Clare (Labour / Le Travail, 2005)
The article reviews the book, "British Trade Unions since 1933," by Chris Wrigley.

La mesure du contrat psychologique dans un contexte de travail francophone - Guerrero, Sylvie (Relations industrielles / Industrial Relations, 2005)
Si le concept de « contrat psychologique » est désormais largement répandu dans la littérature, les instruments de sa mesure font encore défaut. Rousseau a proposé en 1990 le Psychological Contract Index (PCI), qu’elle a actualisé en 1998-2000. Cet article vise à adapter cet outil en France et à le compléter en testant deux mesures de la réalisation du contrat psychologique : une mesure directe et une mesure soustractive. Il pose aussi le problème de la mesure de la réciprocité propre au contrat psychologique et s’appuie sur le modèle de Morrison et Robinson pour tester une relation modératrice entre les scores de réalisation de l’entreprise et ceux de l’employé. Les résultats d’une enquête menée auprès de 217 cadres français confirment partiellement les hypothèses de l’auteure. Ils montrent que la structure factorielle du PCI manque de stabilité et doit faire l’objet de nouvelles recherches quant à sa validité : 14 facteurs sont identifiés au lieu des sept avancés par Rousseau dans le PCI. Conformément aux hypothèses posées, c’est la mesure directe de la réalisation du contrat qui démontre la meilleure validité. En outre, l’auteur valide le rôle modérateur de la réalisation du contrat psychologique par le salarié.

The No-Nonsense Guide to Global Media - Gunster, Shane (Labour / Le Travail, 2005)
The article reviews the book, "The No-Nonsense Guide to Global Media," by Peter Steven.

Le renouveau syndical et la restructuration du travail : Introduction au numéro thématique de Just Labour - Haiven, Larry; Le Queux, Stéphane; Lévesque, Christian; Murray, Gregor (Just Labour: A Canadian Journal of Work and Society, 2005)

Bus Griffiths' Now You're Logging: A Graphic Novel about British Columbia Coastal Logging in the 1930s - Hak, Gordon H. (Gordon Hugh) (Labour / Le Travail, 2005)
A comic book is an unlikely entrée into the history of logging in coastal British Columbia, but Bus Griffiths’ 1978 graphic novel "Now You’re Logging" provides an intriguing window onto work in the woods in the 1930s. Griffiths worked for years as a logger on the coast, experiencing the camps of the 1930s directly. ..."Now You’re Logging" offers a particular version of the loggers’ life, but it still captures many aspects of work in the coastal forests of the 1930s, and does so in an accessible manner. There are many popular histories of British Columbia coastal logging, chock full of photographs, but Griffiths offers black-and-white drawings, and, as bird watchers inspecting field guides know, drawings often provide a more effective way of presentation. As a work of fiction it stands comfortably with other narratives, such as Haig-Brown’s "Timber" and Martin Allerdale Grainger’s "Woodsmen of the West," in giving helpful perspectives on the history of the loggers’ world. –From author's introduction and conclusion

The Corporation: The Pathological Pursuit of Profit and Power/Wealth by Stealth; Corporate Crime, Corporate Law and the Perversion of Democracy - Haley, Ella (Labour / Le Travail, 2005)
The article reviews the book, "Wealth by Stealth: Corporate Crime, Corporate Law and the Perversion of Democracy," by Harry Glasbeek.

La citoyenneté et la reconnaissance du travail féminin : Une convergence souhaitable et nécessaire ? - Hallée, Yves (Relations industrielles / Industrial Relations, 2005)
Cet article se veut une réflexion sur la mise en relation de l’équité salariale avec le concept de citoyenneté. Ainsi, la pérennité de l’équité salariale serait tributaire du partage des valeurs associées au travail féminin et de la reconnaissance collective du « care », le travail centré sur autrui, qui le caractérise. À partir d’un questionnement sur le caractère universel et inclusif de la citoyenneté et sur sa présomption d’égalité, le texte converge vers une représentation citoyenne susceptible de légitimer davantage le travail féminin. De plus, l’impulsion donnée par sa croissance, couplée à une identité imprégnée de valeurs associées au « care », pourraient contribuer à une meilleure reconnaissance salariale. L’équité salariale serait l’expression cohérente et effective d’une citoyenneté, qui passe par une reconnaissance juste et équitable du travail centré sur autrui.

Reforming Pensions in Europe: Evolution of Pension Financing and Sources of Retirement Income - Harvey, Mark (Relations industrielles / Industrial Relations, 2005)
The book Reforming Pensions in Europe: Evolution of Pension Financing and Sources of Retirement Income, by Gerard Hughes and Jim Stewart, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Pension plan funding; Pension plans; Reforms; Retirement; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Duty to Accommodate - Hatfield, Robert (Just Labour: A Canadian Journal of Work and Society, 2005)
Workers traditionally accommodated co-workers. But, as accommodation law developed, tensions emerged. In Meiorin: accommodation is the norm. Employers must eliminate standards, rules, practices, etc. that discriminate on prohibited grounds, up to undue hardship. In the Canadian Human Rights Act, undue hardship includes only cost, health and safety. Other jurisdictions, following Central Alberta Dairy Pool, consider: impact on the collective agreement, other workers’ rights, employee morale, size of operation, workforce and facility adaptability. O’Malley clarifies adverse affect discrimination. A rule, although made in good faith, may discriminate “if it affects a person … differently from others”. Accommodation may override contract provisions (Renaud), including seniority (Goyette). While employers have principal responsibility for accommodation, unions have a role too (Gohm). Unions reduce accommodation tensions by: auditing collective agreements, reviewing accommodation procedures, educating members and leaders.

L’obligation d’adaptation - Hatfield, Robert (Just Labour: A Canadian Journal of Work and Society, 2005)
De tout temps, les travailleurs et les travailleuses se sont accommodés les uns les autres. Cependant, l’adoption de lois sur l’adaptation a semé des tensions entre eux. Avec Meiorin: l’adaptation est la norme. Les employeurs doivent éliminer les normes, règles, pratiques, etc., qui établissent une distinction fondée sur un motif illicite, pourvu que cela ne leur impose pas une contrainte excessive. Dans la Loi canadienne sur les droits de la personne, la contrainte excessive ne comprend que le coût et les considérations relatives à la santé et à la sécurité. Par suite de la décision Central Alberta Dairy Pool, d’autres ressorts tiennent en outre compte des répercussions sur la convention collective, des droits des autres travailleurs et travailleuses, du moral du personnel, de la taille de l’organisation, de son effectif et de sa facilité d’adaptation. La décision O’Malley éclaircit la discrimination par suite d’un effet préjudiciable. Toute règle, même si elle a été adoptée de bonne foi, peut être discriminatoire si elle influence une personne « d'une manière différente par rapport à d'autres personnes visées ». L’obligation d’adaptation peut l’emporter sur les dispositions des conventions collectives (Renaud), y compris celles qui portent sur l’ancienneté (Goyette). Bien que la responsabilité d’adaptation incombe principalement aux employeurs, les syndicats doivent en assumer une partie (Gohm). Les syndicats réduisent les tensions relatives à l’adaptation en vérifiant les conventions collectives, en examinant les procédures d’adaptation et en sensibilisant leurs membres et leurs chefs.

Capital and Community Reconsidered: The Politics and Meaning of Deindustrialization - High, Steven C. (Labour / Le Travail, 2005)
The article reviews and comments on "I Was Content and Not Content: The Story of Linda Lord and the Closing of Penobscot Poultry" by Cedric Chatterley and Alicia J. Rouverol, "Capital Moves: RCA’s 70-Year Quest for Cheap Labor" by Jefferson Cowie, "Beyond the Ruins: The Meaning of Deindustrialization" edited by Jefferson Cowie and Joseph Heathcott, and "Steeltown U.S.A.: Work and Memory in Youngstown," by Sherry Lee Linkon and John Russo.

Race and Politics in Histories of the 20th-century US Working Class - Hinshaw, John Hendrix (Labour / Le Travail, 2005)
The article reviews and comments on "Behind the Backlash: White Working-Class Politics in Baltimore, 1940-1980" by Kenneth D. Durr, "Victory at Home: Manpower and Race in the American South During World War II" by Charles D. Chamberlain, "Civil Rights Unionism: Tobacco Workers and the Struggle for Democracy in the Mid-Twentieth Century South" by Robert Rodgers Korstad, and "Black Freedom Fighters in Steel: The Struggle for Democratic Unionism" by Ruth Needleman.

"The Evils with Which We are Called to Grapple": Élite Reformers, Eugenicists, Environmental Psychologists, and the Construction of Toronto's Working-Class Boy Problem, 1860-1930 - Hogeveen, Bryan (Labour / Le Travail, 2005)
Since the 19th century Toronto, Ontario's working-class delinquent boys have been subjected to intense scrutiny and control. The deviant and criminal conduct that brought working-class juvenile offenders to police and court attention did not change significantly over the late 19th and early 20th centuries. However, how their conduct was understood and governed was in a constant state of change and adjustment. This article explores how Toronto's working-class delinquent boys were represented and governed by elites, reformers, juvenile justice officials, medical experts, and university-trained psychologists from 1860 to 1930. More specifically, it demonstrates how the 19th-century male juvenile offender, judged the product of injurious circumstances, was reinvented by eugenicists as the mentally deficient subject of the late 1910's and again (re)defined as an environmental psychiatric subject after 1925. These representations often overlapped, were discontinued, conflicted, and were in constant tension. Despite theoretical and practical differences, elites, eugenicists, and environmental psychologists were all particularly troubled by working-class male delinquency.

Sweated Work, Weak Bodies: Anti-Sweatshop Campaigns and Languages of Labor - Holmes, John (Labour / Le Travail, 2005)
The article reviews the book, "Sweated Work, Weak Bodies: Anti-Sweatshop Campaigns and Languages of Labor," by Daniel E. Bender.

Machine-breaking in England and France during the Age of Revolution - Horn, Jeff (Labour / Le Travail, 2005)
This essay will attempt to depict the dramatic impact that the violent wrecking of machines had on entrepreneurial decision-making and state action in England and France [in the 18th and 19th centuries]. Resistance to the machine must be situated in its local, regional, national, and international contexts in order to understand the consequences of organized, violent machine-breaking on the course of industrial development. The movements that led to the widespread destruction of machines were organized regionally rather than locally and the patterns of entrepreneurial reaction, technological development, and technology transfer, as well as mechanization, also varied by region. –From author's introduction

Fighting for Dignity: The Ginger Goodwin Story - Isitt, Benjamin (Labour / Le Travail, 2005)
The article reviews the book, "Fighting for Dignity: The Ginger Goodwin Story," by Roger Stonebanks.

Fighting for a Living Wage - Jacobs, Ken (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Fighting for a Living Wage," by Stephanie Luce.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economic policy; Labor Unions; Minimum wage; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; enforcement

The Economics of Affirmative Action - Jain, Harish C. (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "The Economics of Affirmative Action," edited by Harry J. Holzer and David Neumark.
Keywords: Affirmative action; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economic theory; Essays; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Réponses syndicales à la sous-traitance - Jalette, Patrice (Just Labour: A Canadian Journal of Work and Society, 2005)
La sous-traitance est l'un des plus importants défis pour les syndicats à l'heure actuelle. Cet article explore quatre positions syndicales en matière de sous-traitance : opposition, défensive, abstention et offensive. Différents exemples tirés de nos observations sur le terrain permettent d'illustrer ici les différentes attitudes adoptées et les ressources susceptibles d'être mobilisées par les syndicats pour répondre à la sous-traitance. Le principal constat demeure que la réponse syndicale à la sous-traitance est bien souvent plus subtile et nuancée qu'une simple opposition inconditionnelle. Afin de conserver une certaine marge de manœuvre dans le développement et l'adoption d'une position en matière de sous-traitance, il est nécessaire pour un syndicat de travailler sur ses ressources de pouvoir. Quelques pistes sont suggérées pour y parvenir : le développement d'une vision globale, la mobilisation à l'interne, la construction de liens de solidarité à l'externe. // Subcontracting is one of the most important current challenges for unions. This article explores four union positions with regard to subcontracting: oppositional, defensive, abstentionist and proactive. It draws on different examples and cases from the author's research in the field to highlight the different union stances and the resources likely to be mobilized by unions in response to subcontracting. The major finding is that rather than a simple position of unconditional opposition, union responses to subcontracting are highly varied and finely nuanced. Moreover, in order to enlarge its scope to develop a position on subcontracting, a union must work on its power resources. Several avenues are identified in order to reinforce these resources. It was found that a global vision, internal mobilization and the development of solidarity with outside groups all contribute to a greater capacity on the part of the union to deal with subcontracting.

Code Green: Money-Driven Hospitals and the Dismantling of Nursing - Jones, Esyllt (Labour / Le Travail, 2005)
The article reviews the book, "Code Green: Money-Driven Hospitals and the Dismantling of Nursing. Weinberg," by Beth Dana.

Women in Non-Traditional Occupations: Challenging Men - Jurik, Nancy (Labour / Le Travail, 2005)
The article reviews the book, "Women in Non-Traditional Occupations: Challenging Men," by Barbara Bagilhole.

La théorie de la structuration : Une analyse des formes et des dynamiques organisationnelles - Kechidi, Med (Relations industrielles / Industrial Relations, 2005)
L’objectif de cet article est de présenter les concepts et la démarche de la théorie de la structuration d’Anthony Giddens. L’idée fondamentale du modèle de structuration des systèmes sociaux proposé par cet auteur est que les structures, ensemble de règles et de ressources, organisent les activités tout autant que les activités les organisent et leur donnent du sens et une finalité. Cette dualité de l’organisé et de l’organisant débouche sur une conception pertinente de l’action, de la coordination et du changement organisationnel ; elle permet notamment de « faire le pont » entre les dynamiques de structuration individuelles et les dynamiques de structuration collectives.

Ruling Canada: Corporate Cohesion and Democracy - Klassen, Jerome (Labour / Le Travail, 2005)
The article reviews the book, "Ruling Canada: Corporate Cohesion and Democracy," by Jamie Brownlee.

Radio Active: Advertising and Consumer Activism, 1935-1947 - Kuffert, Len (Labour / Le Travail, 2005)
The article reviews the book, "Radio Active: Advertising and Consumer Activism, 1935-1947, by Kathy M. Newman.

Human Capital in the United States from 1975 to 2000 : Patterns of Growth and Utilization - Lavoie, Marie (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Human Capital in the United States from 1975 to 2000 : Patterns of Growth and Utilization," by Robert H. Haveman, Andrew Bershadker and Jonathan A. Schwabish.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Droits de la personne, relations du travail et défis pour les syndicats contemporains - Legault, Marie-Josée (Relations industrielles / Industrial Relations, 2005)
Les chartes des droits de la personne, les lois protégeant ces mêmes droits et la jurisprudence qu’elles engendrent provoquent des bouleversements dans les milieux de travail régis par le droit des rapports collectifs de travail et dans les règles de fonctionnement syndical. Les cas des femmes intégrant des secteurs d’emploi non traditionnellement féminins par le truchement des programmes d’accès à l’égalité et des associations regroupant les syndiqués contestant les effets des clauses de disparité de traitement sont ici utilisés pour illustrer la profondeur du choc entre les nouvelles règles fondées sur l’équité qu’introduisent les droits de la personne et les règles de l’égalité formelle entre syndiqués qui ont traditionnellement régi le fonctionnement syndical.

L'aveuglement organisationnel ou comment lutter contre les malentendus - Legendre, Camille (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "L’aveuglement organisationnel ou comment lutter contre les malentendus," by Valérie Boussard, Delphine Mercier and Pierre Tripier.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Choosing to Labour: Structure and Agency in School-Work Transitions - Lehmann, Wolfgang (Canadian Journal of Sociology, 2005)
We still know relatively little about how young people rationalize their educational and occupational plans and what this might tell us about the relationship between structure and agency in school-work transitions. In this paper, based on a multi-method comparison of youth apprentices in Canada and Germany, the range of school-work transition alternatives realistically under consideration was circumscribed by socio-economic status, habitus, cultural capital, and institutional factors. While their vocational choices reproduced their class position, youth apprentices nevertheless saw their entry into the trades as an expression of a preference for, and identity with, working-class ideals of manual work. Further analysis suggests, however, that these narratives can also be interpreted as post-facto rationalization strategies in response to public discourses that equate life course success with ever higher levels of educational attainment.

Union Disaffection and Social Identity: Democracy as a Source of Union Revitalization - Lévesque, Christian; Murray, Gregor; Queux, Stéphane Le (Work and Occupations, 2005)
This article examines union members’evaluation of the relevance of unions and their identification with a traditional collective value frame for union action. It seeks to take account of the impact of increasing labor market heterogeneity, declining instrumentality, and the behavior of unions and employers. Using Canadian data gathered from individual union members and their local union leaders, the study finds that new labor market identities are notlinked to weaker belief in the relevance of unions but are associated with weaker identification with the traditional value frame. Although declining instrumentality and hostile employer behavior are associated with greater identification with traditional value frames, greater union democracy is associated with less membership disaffection on both the relevance of unions and their collective modes of action. Union democracy is therefore found to be a key tool to address membership disaffection and to generate collective identities for a renewed union project.
Keywords: democracy; labor union; social differentiation; union renewal; workplace

The Workers' Festival: A History Of Labour Day In Canada - Levine, Gil (Just Labour: A Canadian Journal of Work and Society, 2005)
The article reviews the book, "The Workers' Festival: A History Of Labour Day In Canada," by Craig Heron and Steve Penfold.

The Invisible Health Risks of Precarious Employment - Lewchuk, Wayne; De Wolff, Alice; King, Andy; Polanyi, Michael (Association of Industrial Relations Academics of Australia and New Zealand, 2005)
This article reports a new conceptual approach to measuring the characteristics of precarious employment and their effect on health. Our starting point is the Karasek 'job strain' model. We argue that 'job strain' focuses on the health effects of work once people are employed. It is less effective in capturing the health effects associated with the employment relationship, the process by which workers acquire work, keep work and negotiate its terms and conditions. We develop a new construct, 'employment strain' to measure these aspects of work organisation. Evidence presented indicates employment strain is associated with poorer health outcomes.

Union Networks and Global Unionism in Maritime Shipping - Lillie, Nathan (Relations industrielles / Industrial Relations, 2005)
Under the auspices of the International Transport Workers' Federation's (ITF) Flag of Convenience campaign, maritime unions have developed transnational global structures exploiting interdependencies in transportation production chains. The ITF, a London-based association of transport unions, connects the struggles of seafarers and port workers through a global strategy of union networking and coordinated industrial action. Seafaring unions draw on the industrial leverage of port workers to negotiate minimum standard pay agreements, while dock unions leverage the growing influence of the ITF in fighting union busting in ports. A global transnational ship inspector network provides the power basis for imposing collective agreements on shipowners. Although conceived as a resource for organizing seafarers, the inspectorate also provides port unions with leverage.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Business conditions; International; Labor Unions; Maritime industry; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Hidden Knowledge : Organized Labour in the Information Age - Linhart, Danièle (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Hidden Knowledge : Organized Labour in the Information Age," by D. W. Livingstone et Peter H. Sawchuk.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Union Influence on Worker Education and Training in Canada in Tough Times - Livingstone, D. W.; Raykov, Milosh (Just Labour: A Canadian Journal of Work and Society, 2005)
This research has focused on re-analyzing data from previous large-scale Canadian surveys that include information on education and training activities and union status, as well as other demographic and organizational factors, most prominently the 1993 and 1997 Adult Education and Training Surveys. In contrast to some recent studies, we find that union status has had consistent positive individual-level effects in Canada on participation in adult education courses and employer-sponsored courses in general, and especially for women union members. In addition, our analysis of data from the 1998 national survey on informal learning finds that in this much more extensive form of learning, unionized workers are significantly more likely than non-unionized workers to participate in more directly empowering forms of knowledge including learning about workers’ rights and political issues.

Recent Publications in Canadian Labour History - Lonardo, Michael; Sweeny, Robert C.H. (Labour / Le Travail, 2005)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]
Keywords: BIBLIOGRAPHY (Documentation); Working class

Capacity Building - Preparing Caribbean Public Sector Unions for an Economic Environment in Transition - Lorde, Ann-Marie J. (Just Labour: A Canadian Journal of Work and Society, 2005)
This paper seeks to examine the renewal of the Caribbean Public Sector trade unions (CPSU), and make a number of recommendations as it regards the capacity building and institutional strengthening of these unions. The paper begins with an introduction that lays the foundation for the discussion of capacity building for CPSU. It continues with a socio-historical background to the current difficulties facing the CPSU, and continues with an examination of a number of regional concerns for the CPSU. Based on the Regional concerns identified and the fact that CPSU need to step out of their traditional role of representation and, in addition, become concerned with national issues, the paper concludes with a number of recommendations for the way forward for the CPSU. // Cet article examine le renouveau des syndicats du secteur public des Caraïbes (SSPC) et établit un certain nombre de recommandations eu égard à leur capacité de consolidation institutionnelle. L’introduction expose les éléments de fonds qu’il s’agit d’avoir à l’esprit pour comprendre la capacité d’action des SSPC. S’en suivent une présentation des conditions socio-historiques qui expliquent leurs difficultés actuelles, puis un examen des questions régionales auxquelles ils font face. De là, et prenant parti que les SSPC doivent sortir de leur rôle traditionnel de représentation, y inclus une prise en compte des questions nationales, l’article conclut en identifiant des voies d’avenir.

The Future of Worker Representation - Lucio, Miguel Martínez (Relations industrielles / Industrial Relations, 2005)
The book The Future of Worker Representation, edited by Geraldine Healy, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Forecasts; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Workers

Les stratégies des ressources humaines - Malo, François Bernard (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Les strategies des ressources humaines," 3rd edition, by Bernard Gazier.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resources; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Moscow Rules? 'Red' Unionism and 'Class Against Class' in Britain, Canada, and the United States, 1928-1935 - Manley, John (Labour / Le Travail, 2005)
The article analyzes the claims of traditionalist and revisionist historians concerning communism by comparing industrial work of the national socialist parties in Great Britain, the U.S. and Canada in the period 1928-1935. The efforts made by the national parties to strive for leadership of the working class in the workplace are explored. Traditionalist historians are of the opinion that adequate comprehension of communism requires recognition of subordination of each national party to the demands of Moscow, Russia. According to revisionist historians, the national parties enjoyed autonomy in resisting or adapting to the demands of Moscow.
Keywords: Canada; Communism; Comparative studies; GREAT Britain; Labor Unions; SOCIALIST parties; United States; Working class

Real Country: Music and Language in Working-Class Culture - Mann, Geoff (Labour / Le Travail, 2005)
The article reviews the book, "Real Country: Music and Language in Working-Class Culture," by Aaron A. Fox.

The Politics of Prostitution - Maria, Laura (Labour / Le Travail, 2005)
The article reviews the book, "The Politics of Prostitution," edited by Joyce Outshoom.

The Failed Century of the Child: Governing America's Young in the Twentieth Century - Marshall, Dominique (Labour / Le Travail, 2005)
The article reviews the book, "The Failed Century of the Child: Governing America's Young in the Twentieth Century," by Judeith Sealander.

La multiplicité des ancres de carrière chez les ingénieurs québécois : Impacts sur les cheminements et le succès de carrière - Martineau, Yvon; Wils, Thierry; Tremblay, Michel (Relations industrielles / Industrial Relations, 2005)
Le modèle des ancres de carrière proposé par Schein en 1978 est considéré comme une contribution majeure pour comprendre les cheminements de carrière des individus. En fait, cette théorie repose sur le postulat implicite selon lequel un individu ne posséderait qu’une seule ancre dominante. Ce phénomène de dominance est encore appelé « différenciation ». Aussi, de nombreux chercheurs en déduisent-ils qu’il faut ne retenir que l’ancre de carrière ayant le score le plus élevé pour opérationnaliser ce concept de dominance ou de différenciation. Pourtant certains individus pourraient posséder plusieurs ancres élevées, ce qui pose la question de la multiplicité des ancres, ici appelée « indifférenciation ». S’appuyant sur un échantillon de 900 ingénieurs québécois, cette étude montre que « l’indifférenciation » est plus fréquente qu’on ne le pense, qu’elle n’est pas un phénomène pathologique et qu’elle permet de mieux cerner un cheminement de carrière mal connu, soit le cheminement hybride.

Working Like a Homosexual: Camp, Capital, Cinema - Maynard, Steven (Labour / Le Travail, 2005)
The article reviews the book, "Working Like a Homosexual: Camp, Capital, Cinema," by Matthew Tinkcom.

The Tramp Is Back - McCallum, Todd (Labour / Le Travail, 2005)
The article reviews and comments on "The Tramp in America" by Tim Creswell, "Citizen Hobo: How a Century of Homelessness Shaped America" by Todd DePastino, and "Indispensable Outcasts: Hobo Workers and Community in the American Midwest, 1880-1930" by Frank Tobias Higbie.

Initiative individuelle et formation - Méhaut, Philippe (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Initiative individuelle et formation," edited by Fabienne Berton, Mario Correia, Corinne Lespessailles and Madeleine Maillebouis.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Third-Sector Development: Making Up for the Market - Melnyk, George (Labour / Le Travail, 2005)
The article reviews the book, "Third-Sector Development: Making Up for the Market," by Christopher Gunn.

Responsabilité sociale d'entreprise et finance responsable : quels enjeux ? - Mercier, Samuel (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Responsabilité sociale d’entreprise et finance responsable : quels enjeux ?," edited by Diane-Gabrielle Tremblay and David Rolland.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Travail, organisation et santé: le défi de la productivité dans le respect des personnes - Morin, Denis (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Travail, organisation et santé : le défi de la productivité dans le respect des personnes," by Alain Vinet.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Formidable Heritage; Manitoba's North and the Cost of Development 1870 to 1930 - Morrison, William R. (Labour / Le Travail, 2005)
The article reviews the book, "Formidable Heritage: Manitoba's North and the Cost of Development 1870 to 1930, by Jim Mochoruk.

Gurus, Hired Guns, and Warm Bodies: Itinerant Experts in a Knowledge Economy - Mosco, Vincent (Labour / Le Travail, 2005)
The article reviews the book, "Gurus, Hired Guns, and Warm Bodies: Itinerant Experts in a Knowledge Economy," by Stephen R. Barley and Gideon Kunda.

When Coal Was King: Ladysmith and the Coal-Mining Industry on Vancouver Island - Mouat, Jeremy (Labour / Le Travail, 2005)
The article reviews the book, "When Coal Was King: Ladysmith and the Coal-Mining Industry on Vancouver Island," by John R. Hinde.

Conflict between Liberal Economic Ideology and Citizenship at Work - Murray, Georgina (Relations industrielles / Industrial Relations, 2005)
Citizenship in work is a continuous process of sustaining and fighting for just social rights. The argument here is that currently a major impediment to this democratic process at work is the practical and ideological imposition of economic liberal policy, conceived for and by dominant class interests. This article discusses the idea of citizenship, its antithesis economic liberalism and its synthesis Keynesianism and the welfare state. Then it asks what these and other ideas bring to the debate about citizenship and work in a global society?
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Citizenship; Democracy; Economic policy; Labor Unions; Rights; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social classes; Social policy

New Jersey Dreaming: Capital, Culture, and the Class of '58 - Neatby, Nicole (Labour / Le Travail, 2005)
The article reviews the book, "New Jersey Dreaming: Capital, Culture, and the Class of '58. Ortner, Sherry B.

'Fight for Life': Dave Kashtan's Memories of Depression-Era Communist Youth Work - Niergarth, Kirk; Kashtan, Dave (Labour / Le Travail, 2005)
Dave Kashtan, who was born in 1912, reminisces about his life and times in as a young Communist activist in Montreal in the late 1920s and 1930s, during which he visited the Soviet Union and was also jailed for a year for allegedly seditious remarks made at a public meeting in Montreal. Published posthumously, Kashtan's memoir (entitled "Living in One's Time") is introduced and edited by Kirk Niergarth.
Keywords: Canada; KASHTAN; Dave; Labor movement; SOCIAL stratification; Working class

Can Joint Training Increase Union Knowledge and Power? - Olson, Corliss (Just Labour: A Canadian Journal of Work and Society, 2005)
Globalization has been accompanied by a decline in unionization; however, while globalization presents extremely serious challenges to unions, globalization does not necessarily result in weakened unions. It is important for unions to identify and utilize ways to increase and leverage union power that are responsive to the pressures of globalization. Companies frequently introduce training during restructuring efforts aimed at remaining competitive in a global environment. This paper describes a joint union-management training program which offers an example of a pro-active union approach to joint training initiatives. The training took place in early 2004 in a typical paper mill in central Wisconsin. While the training was designed and undertaken in response to various competitive pressures, the content of the training was primarily determined by employee focus groups. The training design is examined against criteria for successful union involvement in joint ventures. The paper argues that, while joint ventures typically address management's production concerns at the expense of labor, a pro-active union can work to ensure that benefits also accrue to the union. Recent literature on union power in a globalized economy suggests that this training model could be used in other industries to enhance union knowledge and power.

Maurice Spector, James R Cannon, and the Origins of Canadian Trotskyism - Palmer, Bryan D. (Labour / Le Travail, 2005)
The article discusses communism in Canada. The study of communism is stated to have generated less new work and little controversy. Issues concerning bureaucratism of Comintern, Stalinization and transformation of the Left in 1920s are explored by comparing the political histories of Maurice Spector and James P. Cannon. In late 1928, Spector and Cannon abandoned Stalinism and embraced Trotskyism. The efforts made by Spector and Cannon to keep alive the revolutionary potential of Bolshevism highlights the importance of the subjective realm in the construction of a left opposition.
Keywords: BUREAUCRATIZATION; CANNON; James Patrick; 1890-1974; COMMUNIST International; Canada; Communism; OPPOSITION (Political science); RIGHT & left (Political science); SPECTOR; Maurice; TROTSKYISM

Le statut d’emploi : Un élément constitutif de la condition sociale ? - Paquet, Esther (Relations industrielles / Industrial Relations, 2005)
Le travail atypique se caractérise par d’importantes disparités de traitements entre les personnes effectuant, au sein d’une même entreprise, des tâches semblables mais ayant des statuts d’emploi différents. Le présent article tente d’établir si le statut d’emploi peut être considéré comme un élément constitutif de la condition sociale au sens de l’article 10 de la Charte des droits et libertés de la personne. Pour ce faire, nous analyserons l’évolution jurisprudentielle de la notion de condition sociale en nous penchant tant sur l’interprétation des tribunaux de droit commun que sur celle du Tribunal des droits de la personne, nous identifierons les éléments objectifs et subjectifs du travail précaire et nous questionnerons l’interprétation de la notion de condition sociale proposée par la Commission des droits de la personne.

Making Class: The YMCA and Workingmen, 1877-1920 - Parnaby, Andrew (Labour / Le Travail, 2005)
The article reviews the book, "Making Men, Making Class: The YMCA and Workingmen, 1877-1920," by Thomas Winter.

Keeping Up with the Dow Joneses: Debt, Prison, Workfare - Peck, Jamie (Labour / Le Travail, 2005)
The article reviews the book, "Keeping Up with the Dow Joneses: Debt, Prison, Workfare," by Vijay Prashad.

Co-operative Values, Institutions and Free Riding in Australia: Can It Learn from Canada? - Peetz, David (Relations industrielles / Industrial Relations, 2005)
While there is a strong logic favouring co-operation, it faces a central problem: the "free rider" or "cheat." Collectives find ways of promoting norms of solidarity and seek regulation to prevent free riding. Around two-fifths of Australian employees covered by collective agreements are free-riding non-members. Evidence suggests that the recent growth of free riding reflects institutional changes and not the decline of co-operative values and the ascendancy of individualism. The Canadian solution to the cheating problem, which is the Rand formula, inspired Australian unions to introduce (excessive) "agency fees" into collective agreements. These were eventually stopped by the state. Alternative models include "social obligation fees" - provisions for employees covered by the agreement to make a contribution to a voluntary organization of their choice.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Cheating; Collective bargaining; Cooperation; International comparisons; Labor Unions; Models; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Values

Individualisation and Resistance at the Coal Face - Peetz, David; Murray, Georgina (Just Labour: A Canadian Journal of Work and Society, 2005)
This paper examines the implementation of a model of systematic individualisation of the employment relationship by a large multinational corporation in Australia, operating with the support of a pro-corporate state, and the nature and effects of resistance. Principally through interviews with affected workers, we show how the symbolic and the real effects of employment practices, relational practices and informational practices were all aimed at removing freedom of association and replacing it with uncontested, union-free managerial control. We consider how workers and their families were affected by these strategies and how they and their union responded. // Cet article examine la mise en place d'un modèle systématique d'individualisation de la relation d'emploi par une grande multinationale australienne, cela avec le support d'un gouvernement partialement favorable au patronat. La nature et l'impact de la résistance des travailleurs syndiqués sont également mis à jour. Nous montrons, principalement à l'appui des témoignages des travailleurs en cause, comment les effets réels ou symboliques des pratiques d'emploi, ceux des pratiques relationnelles et informationnelles ont été utilisés de concert pour dénier la liberté d'association et la remplacer par un contrôle gestionnaire incontestable et exempt de présence syndicale. Nous relatons comment les travailleurs et leurs familles ont souffert de ces stratégies patronales et comment leur syndicat a rétorqué.

La face cachée de l'organisation : groupes, cliques et clans - Pépin, Richard (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "La face cachée de l’organisation : groupes, cliques et clans," by Luc Brunet and André Savoie.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Notebook: Canadian Volunteers in the Spanish Civil War: New Evidence from the Comintern Archives - Petrou, Michael (Labour / Le Travail, 2005)
When the Berlin Wall came down in 1989, symbolically ending the Cold War, few imagined that the resulting shockwaves that toppled the Soviet Union would also reach a perpetually dark and quiet microfilm reading room on the third floor of Library and Archives Canada in Ottawa. But this is what occurred. The disintegration of the Communist order in Russia loosened rigid Soviet control of state archives and made available to Western researchers material which had been inaccessible for the length of the Cold War. This included tens of thousands of documents pertaining to the International Brigades in the Spanish Civil War—foreign volunteers, including roughly 1,600 Canadians, who had been recruited and sent to Spain by the Communist International to fight a fascist rebellion lead by General Francisco Franco. ...In 1993 and 1994, George Bolotenko, an archivist at Library and Archives Canada, visited the Centre for the Preservation and Study of Records of Contemporary History in Moscow, also known as the Comintern Archives, to purchase microfilmed copies of some 10,000 pages of documents on Canadians in the International Brigades. Although the impact of this material on historical scholarship has thus far been light, it has the potential to irrevocably change scholarship on Canadians in the Spanish Civil War. –Author's introduction
Keywords: ARCHIVAL resources; CIVIL War; 1936-1939; Foreign workers; History; SPAIN; VOLUNTARY military service

Walking the Union Walk: Stories from CEP’s First Ten Years - Phillips, Paul (Just Labour: A Canadian Journal of Work and Society, 2005)
Walking the Union Walk: Stories from CEP’s First Ten Years, by Jamie Swift, is reviewed.

From "Old Left" to "New Labour"? Eric Hobsbawm and the Rhetoric of "Realistic Marxism" - Pimlott, Herbert (Labour / Le Travail, 2005)
While the relationships between intellectual research and political commitment, and indeed political engagement, have been identified amongst social, labour, and Marxist historians, such as the Communist Party of Great Britain’s Historians’ Group, there are few, if any, examinations of the rhetorical and communications process by which such public intellectual activity is made: i.e., the “how” of political interventions. This paper addresses this important area in examining the means by which [Eric] Hobsbawm was able to intervene effectively in public debates, having a direct impact on the Labour Party’s future trajectory. Hobsbawm exercised considerable influence in the highly public political infighting within the Labour Party [i.e., Old Left and New Labour], even though he was a member of the Communist Party of Great Britain, and he was able to effect changes through his contributions to debates which affected both political parties simultaneously. –From author's introduction
Keywords: BLAIR; Tony; 1953-; Communism; DEBATES & debating; GREAT Britain; HOBSBAWM; E. J. (Eric J.); 1917-2012; Labor movement; Labor policy; METAPHOR; Public speaking

The Red Man's on the Warpath: The Image of the "Indian" and the Second World War - Pitsula, James M. (Labour / Le Travail, 2005)
The article reviews the book, "The Red Man's on the Warpath: The Image of the "Indian" and the Second World War," by R. Scott Sheffield.

Money in Their Own Name: The Feminist Voice in Poverty Debate in Canada, 1970-1995 - Porter, Ann (Labour / Le Travail, 2005)
The article reviews the book, "Money in Their Own Name: The Feminist Voice in Poverty Debate in Canada, 1970-1995," by Wendy McKeen.

Weapons of Mass Persuasion: Marketing the War against Iraq - Poyntz, Stuart (Labour / Le Travail, 2005)
The article reviews the book, "Weapons of Mass Persuasion: Marketing the War against Iraq," by Paul Rutherford.

An Introduction To “Restructuring Work And Labour In The New Economy” (RWL-INE) - Pupo, Norene (Just Labour: A Canadian Journal of Work and Society, 2005)

Culture and Resistance: Conversations with Edward W. Said - Razack, Sherene H. (Labour / Le Travail, 2005)
The article reviews the book, "Culture and Resistance: Conversations with Edward W. Said," by David Barsamian and Edward W. Said.

A Troublemaker's Handbook 2: How To Fight Back Where You Work - And WIN! - Rebick, Judy (Just Labour: A Canadian Journal of Work and Society, 2005)
A Troublemaker's Handbook 2: How To Fight Back Where You Work - And WIN!, by Jane Slaughter, is reviewed.

Jewish Radicalism In Winnipeg, 1905-1960: Jewish Life and Times, Volume VIII - Reilly, Nolan (Labour / Le Travail, 2005)
The article reviews the book, "Jewish Radicalism in Winnipeg, 1905-1960," edited by Daniel Stone.

From the Lower East Side to Hollywood: Jews in American Popular Culture - Reiter, Ester (Labour / Le Travail, 2005)
The article reviews the book, "From the Lower East Side to Hollywood: Jews in American Popular Culture," by Paul Buhle.

The Historical Origins of an Industrial Disaster: Occupational Health and Labour Relations at the Fluorspar Mines, St. Lawrence, Newfoundland, 1933-1945 - Rennie, Richard (Labour / Le Travail, 2005)
Using union, government, and company records, as well as interviews, this article explores the origins of one of the most notorious industrial disasters in Canadian history - the deaths from industrial disease of some two hundred fluorspar miners on the south coast of Newfoundland. It explores the social, economic, and political forces that shaped the hazards they believed were destroying their health and the response of industry and the state to those efforts. Central to the account is a series of strikes that took place during 1941 and the actions of a government tribunal appointed to settle the dispute. Setting events at St. Lawrence in the context of some of the theoretical and methodological considerations intrinsic to the study of occupational health as a labor relations issue, this article not only adds to the knowledge of the forces that shaped this particular disaster but also represents a contribution to a neglected area of Canadian labor and working-class history.

Unfair Advantage: Workers' Freedom of Association in the United States under International Human Rights Standards - Root, Lawrence S. (Relations industrielles / Industrial Relations, 2005)
The book Unfair advantage: Workers' Freedom of Association in the United States under International Human Rights Standards, by Lance Compa, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Freedom of Association; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Workers

No Collar: The Humane Workplace and Its Hidden Costs - Russell, Jason (Labour / Le Travail, 2005)
The article reviews the book, "No Collar: The Humane Workplace and Its Hidden Costs, by Andrew Ross.

Mapping the Margins: The Family and Social Discipline in Canada, 1700-1975 - Rutherdale, Robert (Labour / Le Travail, 2005)
The article reviews the book, "Mapping the Margins: The Family and Social Discipline in Canada, 1700-1975," edited by Nancy Christie and Michael Gauvreau,

Robitnytsia, Ukrainian Communists, and the 'Porcupinism' Debate: Reassessing Ethnicity, Gender, and Class in Early Canadian Communism, 1922-1930 - Sangster, Joan (Labour / Le Travail, 2005)
The article offers information on the interrelationship between ethnicity, gender and class in Canadian communism in the period 1922-1930. Ethnicity is stated to have been a contested and complex relationship in the Canadian Communist Party, whereas the Ukrainian section of the party is stated to have been numerically strong. The interrelationship between ethnicity, gender and class is examined by analyzing the content of the Canadian Ukrainian newspaper "Robitnytsia." Emphasis is given on the debate concerning women's equality and the role of women in social movement published in the newspaper.
Keywords: Canada; Communism; Communist Party of Canada; Ethnicity; Gender identity; Social classes; Social movements; Women's rights

Flexible Work Arrangements: Conceptualizations and International Experience - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2005)
The book Flexible Work Arrangements: Conceptualizations and International Experience, by Isik Urla Zeytinoglu, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Flexible hours; International comparisons; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Die "Schutzbedürftigte Frau": Zur Konstruktion von Geschlecht durch Mutterschaftsversicherung, Nachtarbeitsverbot und Sonderschutzgesetzgebung - Schade, Rosemarie (The "Vulnerable Woman": The Construction of Gender by Maternity Assurance, Night Work Ban and Special Protection Legislation., 2005)
The article reviews the book, "Die "Schutzbedürftigte Frau": Zur Konstruktion von Geschlecht durch Mutterschaftsversicherung, Nachtarbeitsverbot und Sonderschutzgesetzgebung," edited by Regina Wecker, Brigitte Studer, and Gaby Sutter.

History of Social Work in Europe 1900-1960: Female Pioneers and their Influence on the Development of International Social Organizations - Schade, Rosemarie (Labour / Le Travail, 2005)
The article reviews the book, "History of Social Work in Europe 1900-1960: Female Pioneers and their Influence on the Development of International Social Organizations," edited by Sabine Hering and Berteke Waaldijk.

The Global Union Research Network: A Potential for Incremental Innovation? - Schmidt, Verena (Just Labour: A Canadian Journal of Work and Society, 2005)
One of the current paradoxes for trade unions is that organizing is an essentially local or national affair whilst the most pressing challenge for unions, which is globalization, can only be faced in a global context. This paper analyzes to what extent the Global Union Research Network (GURN) has the potential to be regarded as an incremental innovation for research within the international labour movement. The paper argues that the GURN can become an incremental innovation and there are three stages to this argument. Firstly the GURN in conceptualized within the international trade union movement. Secondly the term 'innovation' is defined and the GURN is presented as a potential, albeit incremental, innovation. The final stage examines GURN sustainability and the barriers to its institutionalization.

Sexual Harassment Investigations: How to Limit Your Liability and More: A Practical Guide - Shebib, Maureen E. (Relations industrielles / Industrial Relations, 2005)
The book Sexual Harrassment Investigations: How to Limit Your Liability and More: A Practical Guide, by Arjun P. Aggarwal and Madhu M. Gupta, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Investigations; Labor Unions; Liability; Sexual harassment; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Contingent Employment in Europe and the United States - Shields, John (Labour / Le Travail, 2005)
The article reviews the book, "Contingent Employment in Europe and the United States," edited by Ola Bergström and Donald Storrie.

The Nonprofit Sector in Interesting Times: Case Studies in a Changing Sector - Shields, John (Labour / Le Travail, 2005)
The article reviews the book, "The Nonprofit Sector in Interesting Times: Case Studies in a Changing Sector," edited by Kathy L. Brock and Keith G. Banting.

Pratiques en GRH et engagement des employés : Le rôle de la justice - Simard, Gilles; Doucet, Olivier; Bernard, Sarah (Relations industrielles / Industrial Relations, 2005)
En s’appuyant sur la théorie de l’échange social, cet article rend compte de l’effet médiateur des différentes formes de justice organisationnelle (distributive, procédurale, interactionnelle) dans la relation entre les pratiques en gestion des ressources humaines (GRH) inspirées du modèle de Lawler (1986) et l’engagement affectif. Les 134 répondants sont des directeurs aux services financiers d’une institution bancaire située au Québec. Des analyses de régression, effectuées selon les procédures de Kenny, Kashy et Bolger (1998), ont confirmé l’hypothèse de recherche. Ainsi, les résultats font ressortir que la perception de chacune des formes de justice organisationnelle représente une variable médiatrice essentielle pour que la mise en place des pratiques en GRH contribue efficacement au développement et à la consolidation de l’engagement des employés envers leur organisation.

The Effects of the Use of Striker Replacement Workers in Canada: An Analysis of Four Cases - Singh, Parbudyal; Zinni, Deborah M.; Jain, Harish C. (Labor Studies Journal, 2005)
The use of striker replacements is one of the most controversial and emotional issues facing those involved with the industrial relations system. However, a paucity of research has been done on the actual use of replacement workers and how that affects industrial relations outcomes, such as strike activity. Initial research suggests that the use of replacements is associated with longer strikes, supporting the con tention that the use of replacements should be prohibited. Using four case studies, we explore some of the dynamics of strikes that utilize replacements versus those that do not. The results suggest that, in ad dition to economic factors, social and psychological variables may be intricately linked to the relationship between the use of replacements and strike activity.
https://citeseerx.ist.psu.edu/document?repid=rep1&type=pdf&doi=f12d22c06914a64893b0e07132ea9ff85fddd8c6

Death by Consumption - Soron, Dennis (Labour / Le Travail, 2005)
The article reviews and comments on "State of the World 2004. Special Focus: The Consumer Society" by the Worldwatch Institute, edited by Linda Starke, "The High Price of Materialism" by Tim Kasser, and "The Consumer Trap: Big Business Marketing in American Life" by Michael Dawson.

Managing Employment Change - Soussi, Sid Ahmed (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Managing Employment Change," by Huw Beynon, Damian Grimshaw, Jill Rubery and Kevin Ward.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Hidden Knowledge: Organized Labour in the Information Age - Spencer, Bruce (Labour / Le Travail, 2005)
The article reviews the book, "Hidden Knowledge: Organized Labour in the Information Age," by D.W. Livingstone and Peter H. Sawchuck.

Workplace Learning: A Critical Introduction - Spencer, Bruce (Labour / Le Travail, 2005)
The article reviews the book, "Workplace Learning: A Critical Introduction," by John Bratton et al.

"In case you hadn't noticed!": Race, Ethnicity, and Women's Wage-Earning in a Depression-Era City - Srigley, Katrina (Labour / Le Travail, 2005)
Unites an extensive collection of oral histories with the documentary record - newspapers, the census, and other government records - to examine women's employment during the Great Depression in Toronto, Ontario, discussing how privilege and disadvantage based on race and ethnicity, gender, and class influenced women's work experiences. In Toronto's garment industry and as clerical workers, domestics, and teachers, the women in this study had various levels of economic stability, came from varied ethnic and racial backgrounds, and enjoyed, as a consequence, different job options in a period when employment access was particularly important for women and their families. This article explores the intersection between identity and job access to show why this was so in the 1930's. Ultimately, individual experiences indicate that gender should not be given analytical predominance for understanding all depression-era labor markets. In some historical contexts and for some women, gender had less relevance to their experiences than race, ethnicity, or class.

Corporate Governance in Global Capital Markets - Stanford, Jim (Labour / Le Travail, 2005)
The article reviews the book, "Corporate Governance in Global Capital Markets," edited by Janis Sarra.

The Oriental Question: Consolidating a White Man's Province, 1914-1941 - Stanley, Timothy J. (Labour / Le Travail, 2005)
The article reviews the book, "The Oriental Question: Consolidating a White Man's Province, 1914-1941," Patricia E. Roy.

Naming the System: Inequality and Work in the Global Economy - Stevenson, Paul (Labour / Le Travail, 2005)
The article reviews the book, "Naming the System: Inequality and Work in the Global Economy," by Michael D. Yates.

Union Power: The Charged Politics of Electricity in Ontario - Swift, Jamie; Stewart, Keith (Just Labour: A Canadian Journal of Work and Society, 2005)
A neoliberal electricity privatization experiment in Ontario, Canada’s largest province, was supposed to eliminate one of the country’s biggest public utilities and introduce market discipline to the system. The grand experiment would begin in 2001. But an activist campaign by an opposition coalition initiated by electricity workers was crucial in turning back the market-oriented reforms, and indeed turning it into one of the great political train-wrecks in Ontario history.

Going Public: The Role of Labor-Management Relations in Delivering Quality Government Services - Swimmer, Gene (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, Going Public: The Role of Labor-Management Relations in Delivering Quality Government Services," edited by Jonathan Brock and David B. Lipsky.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Essays; Government services; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Great Land Rush and the Making of the Modern World, 1650-1900: Land, Power, and Economics on the Frontier of Upper Canada - Teeple, Gary (Labour / Le Travail, 2005)
The article reviews the book, "Land, Power, and Economics on the Frontier of Upper Canada," by John Clarke.

Challenging The Market: The Stuggle To Regulate Work And Income - Thomas, Mark (Just Labour: A Canadian Journal of Work and Society, 2005)
The article reviews the book, "Challenging The Market: The Stuggle To Regulate Work And Income," edited by Jim Stanford and Leah F. Vosko.

Globalization Under Fire - Thomas, Mark (Labour / Le Travail, 2005)
The article reviews and comments on "The Children of NAFTA: Labor Wars on the U.S./Mexico Border" by David Bacon, "Juggernaut Politics: Understanding Predatory Globalization" by Jacques B . Gelinas, "Labour and Globalisation: Results and Prospects" edited by Ronaldo Munck, and "System in Crisis: The Dynamics of Free Market Capitalism" by James Petras and Henry Veltmeyer.

Representations of a Radical Historian; System Failure: The Breakdown of the Post-War Settlement and the Politics of Labour in Our Time - Thorn, Brian T.; Palmer, Bryan D. (Labour / Le Travail, 2005)
The notebook opens with "Representations of a Radical Historian," a review of "You Can’t Be Neutral on a Moving Train," a documentary on Howard Zinn by Deb Ellis and Denis Mueller (78 minutes, colour, (Brooklyn 2004)). In the second part, entitled "System Failure: The Breakdown of the Post-War Settlement and the Politics of Labour in Our Time," Bryan D. Palmer presents a revised version of an "educational and agitational address" given to the Alberta Federation of Labour's membership forum on 7 May 2004 in the aftermath of the British Columbia hospital and long-term care workers' strike.

From the 'Original Affluent Society' to the 'Unjust Society': A Review Essay on Native Economic History in Canada - Tough, Frank (Journal of Aboriginal Economic Development, 2005)
This essay will initiate an assessment of the literature that actually seeks to explain the economic relationships between Natives and Whites. This review is not a detailed empirical study of a particular aspect of Native economic history or a demonstration of the immediate relevance of economic history. Instead, the present-day need for an accessible account, summary and analysis of the existing economic history literature and a critical evaluation of this disparate body of work will be addressed by this essay. By summarizing and reviewing this disparate literature, a rough chronology of Native economic history can trace major changes. Innovative studies using interesting data sources and methods will be highlighted. The examination of economic history before 1870 will focus on the fur trade to consider exchange relations, racial stratification, credit, and resource management problems. The period following 1870 will consider how the social overhead of the fur trade became a government responsibility. –From Introduction

The Accidental Republic: Crippled Workingmen, Destitute Widows, and the Remaking of American Law - Tucker, Eric (Labour / Le Travail, 2005)
The article reviews the book, "The Accidental Republic: Crippled Workingmen, Destitute Widows, and the Remaking of American Law," by John Fabian Witt.

Booze: A Distilled History - Tufts, Steven (Just Labour: A Canadian Journal of Work and Society, 2005)
Booze: A Distilled History, by Craig Heron, is reviewed.

Work and Labour in Canada: Critical Issues - Tufts, Steven (Just Labour: A Canadian Journal of Work and Society, 2005)
Work and Labour in Canada: Critical Issues, by Andrew Jackson, is reviewed.

Family Quarrel: Joe Salsberg, the'Jewish' Question, and Canadian Communism - Tulchinsky, Gerald (Labour / Le Travail, 2005)
A biography of communist Joseph Baruch Salsberg is presented. He was born in 1902 in Lagov, Poland and had immigrated to Canada in 1913 with his parents. In his 30-year career in the Labor-Progressive Party of Canada (LPP), he and several Jewish radicals propagated the notion that communism results in a better world and provides solution to several problems including the Jewish question. According to Salsberg, antisemitism is prevalent in the Soviet Union.
Keywords: ANTISEMITISM; Communism; LABOR parties; SALSBERG; Joseph Baruch

Waterfront Revolts: New York and London Dockworkers, 1946-61 - Turnbull, Peter (Labour / Le Travail, 2005)
The article reviews the book, "Waterfront Revolts: New York and London Dockworkers, 1946-61," by Colin J. Davis.

Job Stress, Depression and Work-to-Family Conflict: A Test of the Strain and Buffer Hypotheses - Wallace, Jean E. (Relations industrielles / Industrial Relations, 2005)
In this paper, the Job Demand-Control (JDC) model is used to predict depression and work-to-family conflict for married lawyers working full-time. The objectives of this paper are: (1) to determine whether the JDC model applies to work-to-family conflict; (2) to incorporate domain-specific job demand and job control variables; and (3) to examine a wider array of different forms of social support. First, the JDC model also helps explain work-to-family conflict. Second, domain-specificity does not appear key to documenting the buffering effects for job control. Third, spouse's support of one's career has the strongest main effect on both depression and work-to-family conflict, whereas coworker support functions as a moderator of lawyers' job demands and has both buffering and amplifying effects. This paper closes by discussing the possible conditions under which members of support systems may transfer or exacerbate stress effects rather than alleviate them.
Keywords: Attorneys; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Families & family life; Labor Unions; Models; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social support; Stress; Studies; Work life balance

Are Activation Policies Converging in Europe? The European Employment Strategy for Young People - White, Michael (Relations industrielles / Industrial Relations, 2005)
The article reviews the book< Are Activiation Policies Converging in Europe? The European Employment Strategy for Young People," edited by Amparo Serrano Pascual.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social policy; Young adults

Caring For/Caring About: Women, Home Care and Unpaid Caregiving - Whitney, Laurel (Labour / Le Travail, 2005)
The article reviews the book, "Caring For/Caring About: Women, Home Care and Unpaid Caregiving," edited by Karen R. Grant et al.

Eugene A. Forsey: An Intellectual Biography - Wiseman, Nelson (Labour / Le Travail, 2005)
The article reviews the book, "Eugene A. Forsey: An Intellectual Biography," by Frank Milligan.

Imperialism and Disorder: The Global Ambitions and Internal Decay of the United States - Wood, Geoffrey (Labour / Le Travail, 2005)
The article reviews and comments on "Incoherent Empire" by Michael Mann, "Contours of Descent: US Economic Fractures and the Landscape of Global Austerity" by Robert Pollin, and "Tyranny in America: Capitalism and National Decay" by Neal Wood.

Non-Standard Work and Benefits: Has Anything Changed since the Wallace Report? - Zeytinoglu, Isik Urla; Cooke, Gordon B. (Relations industrielles / Industrial Relations, 2005)
This paper examines whether there has been improvement in benefits coverage for non-standard workers since the Wallace Report in 1983. This study uses Statistics Canada's Workplace and Employee Survey (WES) 1999 data. Results show significant differences in the receipt of benefits among non-standard workers, suggesting heterogeneity within this group of workers in terms of benefits coverage. Regular part-time and temporary full-time workers receive fewer benefits than regular full-time workers. Temporary part-time workers have significantly less likelihood of receiving benefits than the other three groups of workers. Overall, results show that since the Wallace Report findings, there has been little improvement in benefits coverage for non-standard workers, and they continue to be relatively disadvantaged in comparison to regular full-time workers.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employee benefits; Labor Unions; Part time employment; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Temporary employment

The Voice of Southern Labor: Radio, Music, and Textile Strikes, 1929-1934 - Zieger, Robert H. (Labour / Le Travail, 2005)
The article reviews the book, "The Voice of Southern Labor: Radio, Music, and Textile Strikes, 1929-1934," by Vincent J. Roscigno and William F. Danaher.

An Exploratory Study of Graduate Student Unions in Canada - Zinni, Deborah; Singh, Parbudyal; MacLennan, Anne (Relations industrielles / Industrial Relations, 2005)
Graduate student unions are beginning to attract attention in Canada and the United States. In Canada, unionization on campuses is especially important for organized labour, as union density has dropped below 30 percent for the first time in five decades. Graduate student unionization is also important in the wider context of precarious employment in North America. Despite the decline in overall union density, graduate student unions have continued to grow in the past decade. However, there is a paucity of scholarly research in this area. In this article, we trace the historical origins of graduate student unions in Canada, discuss relevant legal concerns, analyze pertinent collective bargaining and strike issues, and suggest avenues for future research.